Attaining organisational agility through competitive intelligence: the roles of strategic flexibility and organisational innovation. (17th February 2022) - Atkinson, Peter; Hizaji, Mohammad; Nazarian, Alireza; Abasi, Ahmad
Abstract : Organisational agility can play an important role in an organisation's emergent strategy for survival in an increasingly competitive market-place. This paper examines the impact of competitive intelligence on organisational agility through strategic flexibility and organisational innovation. We gathered data from 83 agency managers of insurance companies in Iran, using random simple sampling. These were analysed using structural equation modelling (SEM) with partial least squares (PLS). Competitive intelligence was found to have an indirect influence on organisational agility through strategic flexibility, which was a mediating variable. Though competitive intelligence influenced organisational innovation organisational innovation did not have a significant effect on organisational agility. Our research contributes to the organisational agility literature by showing that organisational agility is influenced by competitive intelligence but organisational innovation is not as significant as has been assumed, instead strategic flexibility is a more important factor and suggests the human factor may be key to a successful strategy.